2002
DOI: 10.1021/bi015936e
|View full text |Cite
|
Sign up to set email alerts
|

Structure−Activity Relationship of Hydroxamate-Based Inhibitors on the Secretases that Cleave the Amyloid Precursor Protein, Angiotensin Converting Enzyme, CD23, and Pro-Tumor Necrosis Factor-α

Abstract: Multiple proteins are proteolytically shed from the membrane, including the amyloid precursor protein (APP) involved in Alzheimer's disease, the blood pressure regulating angiotensin converting enzyme (ACE), the low affinity IgE receptor CD23, and the inflammatory cytokine tumor necrosis factor-alpha (TNF-alpha). The inhibitory effect of a range of hydroxamic acid-based compounds on the secretases involved in cleaving and releasing these four proteins has been examined to build up a structure-activity relation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
41
1

Year Published

2003
2003
2012
2012

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 46 publications
(42 citation statements)
references
References 55 publications
0
41
1
Order By: Relevance
“…The β-CH bond of valine in Ac-Val-Ala-OMe (11) reacted to a lower extent, as in the simpler case 8, N-Ac-Val(β-OH)-Ala-OMe (11a) being produced in 12% yield (entry 5). N-Ac-Leu-Val-OMe (12) and…”
Section: Resultsmentioning
confidence: 99%
“…The β-CH bond of valine in Ac-Val-Ala-OMe (11) reacted to a lower extent, as in the simpler case 8, N-Ac-Val(β-OH)-Ala-OMe (11a) being produced in 12% yield (entry 5). N-Ac-Leu-Val-OMe (12) and…”
Section: Resultsmentioning
confidence: 99%
“…For stable transfections, 30 g of DNA was introduced to cells by electroporation, and selection was performed in normal growth medium containing 500 g/ml neomycin selection antibiotic. SB 244000 and all other hydroxamate-based inhibitor compounds were synthesized at GlaxoSmithKline Pharmaceuticals (Harlow, UK) and were used at 20 M. Structural details of these compounds have been published previously (25). Phorbol myristate acetate (PMA), filipin, and M␤CD (Sigma) were used at 1 M, 10 nM, and 5 mM, respectively.…”
Section: Methodsmentioning
confidence: 99%
“…APP is expressed endogenously in SH-SY5Y cells; therefore, its shedding can be compared directly with that of PrP overexpressed in the same cells. Cells were incubated in the absence or presence of a range of zinc metalloprotease hydroxamate-based inhibitors (25). Conditioned media were immunoblotted with the APP monoclonal antibody 6E10 (Fig.…”
Section: Metalloprotease-mediated Prp Shedding Is Similar To That Of mentioning
confidence: 99%
“…Although the ACE secretase has not yet been identified, studies with a range of hydroxamic acid-based inhibitors have shown that it has a remarkably similar inhibition profile to the amyloid precursor protein α-secretase, leading to the conclusion that the two secretases are, at the very least, closely related (65). Human plasma ACE originates from endothelial cells, while in other body fluids ACE originates from epithelial, endothelial, or germinal cells (66).…”
Section: Ii-metabolism Of Kininsmentioning
confidence: 99%